Use of an Individualized Relaxation Technique Using Raga Darbari for Rehabilitation of Pediatric Spinal Cord Injury: A Case Report - Pallavi Rameshwar Palaskar; Namrata Sant (Institute of Medico-legal Publications Pvt Ltd, 2021)
Introduction:- A 14 years old male child with spinal cord injury faced great difficulties during transitionand walking with HKFO and walker due to autonomic dysreflexia.Methods: - A child with thoracic D3-D9 spinal cord injury was included in the study .After dischargefrom hospital; he came to physiotherapy OPD regularly. He had achieved sitting with support by 9-10weeks, floor to bed transitions by 11-12 weeks, sit to stand with HKAFO with walker and parallel bar by 12weeks, walking with walker with HKFO (indoor) BY 13 weeks. During the transitions he was suffering fromraised blood pressures and palpitation and flushes. Fluctuation in vitals indicated episodes of autonomicdysreflexia. But day by day he was having less tolerance to therapy and he had started losing confidencein performing transitions and wheel chair rehabilitation, an individualized relaxation therapy Raga Darbariof Indian classical music in instrumental form of FLUTE to induce relaxation in him. Post physiotherapyand post transitions, child was given relaxation for 20-25 minutes and vitals were recorded pre and postrelaxation therapy on day 1 and after last session of 4 weeks of relaxation therapy.Results: - Post 4 weeks of relaxation therapy the child has more stable vital parameters after the transitions,gait training. Frequency of episodes of autonomic dysreflexia was also reduced.Conclusion:- An individualized relaxation therapy using Raga Darbari of Indian Classical music in theinstrumental form has given satisfactory results for autonomic dysreflexia